Long Non-Coding RNA NR-133666 Promotes the Proliferation and Migration of Fibroblast-Like Synoviocytes Through Regulating the miR-133c/MAPK1 Axis - Zhang, Nanwen; Zheng, Ningning; Luo, Dunxiong; Lin, Duoduo; Que, Wenzhong; Wang, He; Huang, Qiuping; Yang, Juhua; Ye, Jian; Chen, Xiaole (Frontiers in Pharmacology, 2022)
Long non-coding RNA (lncRNA) is involved in the regulation of rheumatoid arthritis (RA) and many other diseases. In this study, a new lncRNA, NR-133666, was identified to be highly expressed in the adjuvant-induced arthritis (AIA) rat model using the Agilent lncRNA microarray assay. qRT-PCR verified that NR-133666 was upregulated in fibroblast-like synoviocyte (FLS) of a collagen-induced arthritis (CIA) rat model. FISH analysis showed that NR-133666 is mainly expressed in the cytoplasm of CIA FLS. MTT assay and EdU staining results showed that the proliferation of CIA FLS was inhibited after NR-133666 was knocked down, and the wound healing assay showed that the migration of CIA FLS was also suppressed. Dual luciferase detection was used to confirm the relationship among NR-133666, miR-133c and MAPK1. MAPK1 is the target gene of miR-133c, where NR-133666 acts as a sponge of miR-133c to reduce the inhibitory effect of miR-133c on MAPK1. Overexpression of NR-133666 and MAPK1 can promote the proliferation and migration of CIA FLS, and overexpression of miR-133c can reverse this phenomenon. Western blot indicated that it may be related to the ERK/MAPK signaling pathway. Collectively, we identified that lncRNA NR-133666 acted as a miR-133c sponge that can promote the proliferation and migration of CIA FLS through regulating the miR-133c/MAPK1 axis.